Islamic Education Management in the Thought of Ibn Sina: Between Rationality and Spirituality - Zainuri, Zainuri; Aslamiyah, Nurul (Journal Corner of Education, Linguistics, and Literature, 2024)
Ibn Sina, as a prominent philosopher and Muslim scientist, offered profound thoughts on education that emphasize the balance between intellectual and moral aspects. According to Ibn Sina, education not only aims to enlighten the mind but also to shape the moral and spiritual character of students. This study aims to examine the concept of Islamic education management in the thought of Ibn Sina, focusing on the integration of rationality and spirituality as the foundation for managing education. Ibn Sina, as a prominent philosopher and Muslim scientist, not only made significant contributions in the fields of medicine and philosophy but also had profound thoughts on education. In his view, education must shape a person holistically, being intellectually sharp and spiritually mature. A qualitative approach is used in this study with a literature review method of Ibn Sina’s major works, such as Kitab al-Shifa and Kitab al-Najat, as well as relevant secondary literature. The study’s results show that Ibn Sina emphasized the importance of a logical and systematic teaching method, yet still framed within ethical and religious values. This thought is relevant in the context of contemporary Islamic education management, which faces the challenge of balancing the cognitive and affective aspects of students. Thus, Islamic education management based on Ibn Sina's thought offers an integrative model that combines intellect and spirituality in the educational process sustainably. The thought of Ibn Sina offers a holistic and sustainable model of Islamic education management. This model integrates rationality and spirituality, making it a strong foundation for building an educational system that not only focuses on intellectual achievement but also on the formation of a solid moral character. Thus, Islamic education management based on Ibn Sina’s thought holds great potential to address contemporary educational issues that are often trapped in the separation between knowledge and spiritual values